Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2000
DOI: 10.1115/2000-gt-0535
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a Semi-Closed Cycle, Turboshaft Gas Turbine Engine

Abstract: A semi-closed cycle, turboshaft gas turbine engine was assembled and tested under a cooperative program funded by the NASA Glenn Research Center with support from the U.S. Army. The engine, called HPRTE (High Pressure, Recuperated Turbine Engine), features two distinct cycles operating in parallel; an “inner,” high pressure, recuperated cycle, in which exhaust gas is recirculated, and an “open” through-flow cycle. Recuperation is performed in the “inner,” high pressure loop, which greatly reduces the size of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The recirculation ratio of the first can be better adjusted to keep the high pressure components close to their peak efficiency, as also shown in Ref. (7). This is only partially achievable with the Coleman cycle arrangement as less feedback flow rate is available and sufficient power has to be extracted from the LPT.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The recirculation ratio of the first can be better adjusted to keep the high pressure components close to their peak efficiency, as also shown in Ref. (7). This is only partially achievable with the Coleman cycle arrangement as less feedback flow rate is available and sufficient power has to be extracted from the LPT.…”
Section: Resultsmentioning
confidence: 92%
“…Ref. (7) has shown that the HPRTE arrangement presents a much flatter SFC curve at part-power off-design operating points with respect to conventional configuration. This aspect has been confirmed by this analysis as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting heat exchanged engine concept, but based on an even more complex mechanical arrangement, is the semi‐closed cycle (Rodgers, 1999; Meitner and Senick, 2000). The turboprop concept shown on Figure 12 shows intercooling and recuperation.…”
Section: Small Heat Exchanged Engine Conceptsmentioning
confidence: 99%